Cancer Predisposition Syndromes Associated With Pediatric High-Grade Gliomas - Ceglie, Giulia; Del Baldo, Giada; Agolini, Emanuele; Rinelli, Martina; Cacchione, Antonella; Del Bufalo, Francesca; Vinci, Maria; Carta, Roberto; Boccuto, Luigi; Miele, Evelina; Mastronuzzi, Angela; Locatelli, Franco; et al. (Frontiers in Pediatrics, 2020)
Pediatric High-Grade Gliomas (pHGG) are among the deadliest childhood brain tumors and can be associated with an underlying cancer predisposing syndrome. The thorough understanding of these syndromes can aid the clinician in their prompt recognition, leading to an informed genetic counselling for the family and to a wider understanding of the specific genetic landscape of the tumor when choosing specific therapies. In this review, we summarize the main pHGG-associated cancer predisposing conditions, providing a guide for suspecting these syndromes and referring for genetic counseling.